Chemotherapeutic xCT inhibitors sorafenib and erastin unraveled with the synaptic optogenetic function analysis tool - Dahlmanns, Marc; Yakubov, Eduard; Chen, Daishi; Sehm, Tina; Rauh, Manfred; Savaskan, Nicolai; Wrosch, Jana Katharina (Cell Death Discovery, 2017)
In the search for new potential chemotherapeutics, the compounds' toxicity to healthy cells is an important factor. The brain with its functional units, the neurons, is especially endangered during the radio- and chemotherapeutic treatment of brain tumors. The effect of the potential compounds not only on neuronal survival but also neuronal function needs to be taken into account. Therefore, in this study we aimed to comprehend the biological effects of chemotherapeutic xCT inhibition on healthy neuronal cells with our synaptic optogenetic function analysis tool (SOFA). We combined common approaches, such as investigation of morphological markers, neuronal function and cell metabolism. The glutamate-cystine exchanger xCT (SLC7A11, system Xc-) is the main glutamate exporter in malignant brain tumors and as such a relevant drug target for treating deadly glioblastomas (WHO grades III and IV). Recently, two small molecules termed sorafenib (Nexavar) and erastin have been found to efficiently block xCT function. We investigated neuronal morphology, metabolic secretome profiles, synaptic function and cell metabolism of primary hippocampal cultures (containing neurons and glial cells) treated with sorafenib and erastin in clinically relevant concentrations. We found that sorafenib severely damaged neurons already after 24 h of treatment. Noteworthy, also at a lower concentration, where no morphological damage or metabolic disturbance was monitored, sorafenib still interfered with synaptic and metabolic homeostasis. In contrast, erastin-treated neurons displayed mostly inconspicuous morphology and metabolic rates. Key parameters of proper neuronal function, such as synaptic vesicle pool sizes, were however disrupted following erastin application. In conclusion, our data revealed that while sorafenib and erastin effectively inhibited xCT function they also interfered with essential neuronal (synaptic) function. These findings highlight the particular importance of investigating the effects of potential neurooncological and general cancer chemotherapeutics also on healthy neuronal cells and their function as revealed by the SOFA tool.
EVALuna2:33743

Common network effect-patterns after monoamine reuptake inhibition in dissociated hippocampus cultures - Trepl, Julia; Dahlmanns, Marc; Kornhuber, Johannes; Groemer, Teja W.; Dahlmanns, Jana (Journal of Neural Transmission, 2022)
The pharmacological treatment of major depressive disorder with currently available antidepressant drugs is still unsatisfying as response to medication is delayed and in some patients even non-existent. To understand complex psychiatric diseases such as major depressive disorder and their treatment, research focus is shifting from investigating single neurons towards a view of the entire functional and effective neuronal network, because alterations on single synapses through antidepressant drugs may translate to alterations in the entire network. Here, we examined the effects of monoamine reuptake inhibitors on in vitro hippocampal network dynamics using calcium fluorescence imaging and analyzing the data with means of graph theoretical parameters. Hypothesizing that monoamine reuptake inhibitors operate through changes of effective connectivity on micro-scale neuronal networks, we measured the effects of the selective monoamine reuptake inhibitors GBR-12783, Sertraline, Venlafaxine, and Amitriptyline on neuronal networks. We identified a common pattern of effects of the different tested monoamine reuptake inhibitors. After treatment with GBR-12783, Sertraline, and Venlafaxine, the connectivity degree, measuring the number of existing connections in the network, was significantly decreased. All tested substances led to networks with more submodules and a reduced global efficiency. No monoamine reuptake inhibitor did affect network-wide firing rate, the characteristic path length, or the network strength. In our study, we found that monoamine reuptake inhibition in neuronal networks in vitro results in a sharpening of the network structure. These alterations could be the basis for the reorganization of a large-scale miswired network in major depressive disorder.
CRIS-Team Scopus Importer:2022-03-04
Keywords: Antidepressants; Connectivity; Hippocampal networks; Hippocampus culture; Monoamine reuptake inhibitors

Correction to: Common network effect‑patterns after monoamine reuptake inhibition in dissociated hippocampus cultures (Journal of Neural Transmission, (2022), 129, 3, (261-275), 10.1007/s00702-022-02477-6) - Trepl, Julia; Dahlmanns, Marc; Kornhuber, Johannes; Grömer, Teja Wolfgang; Dahlmanns, Jana (Journal of Neural Transmission, 2022)
The Acknowledgements section was missing from this article and should have read: The present work was performed in (partial) fulfillment of the requirements for obtaining the degree "Dr. med."/"Dr. med. dent. The original article has been corrected.
CRIS-Team Scopus Importer:2022-10-21

Corrigendum: Feasibility and Diagnostic Accuracy of Ischemic Stroke Territory Recognition Based on Two-dimensional Projections of Three-dimensional Diffusion MRI Data - Wrosch, Jana Katharina; Volbers, Bastian; Gölitz, Philipp; Gilbert, Daniel; Schwab, Stefan; Dörfler, Arnd; Kornhuber, Johannes; Groemer, Teja Wolfgang (Frontiers in Neurology, 2017)
[This corrects the article on p. 239 in vol. 6, PMID: 26635717.].
EVALuna2:22534

Effects of activin A on hippocampal network activity - Dahlmanns, Marc; Dahlmanns, Jana; Zheng, Fang; Alzheimer, Christian (ACTA PHYSIOLOGICA, 2019)
CRIS-Team WoS Importer:2019-11-12

Environmental enrichment recruits activin A to recalibrate neural activity in mouse hippocampus - Dahlmanns, Marc; Dahlmanns, Jana; Schmidt, Carla C.; Valero Aracama, Maria Jesus; Zheng, Fang; Alzheimer, Christian (Cerebral Cortex, 2022)
The TGF-beta family member activin A modulates neural underpinnings of cognitive and affective functions in an activity-dependent fashion. We have previously shown that exploration of a novel and enriched environment (EE) strongly enhanced activin signaling. Whereas the many beneficial effects of EE are amply documented, the underlying mechanisms remain largely elusive. Here, we examined the hypothesis that EE recruits activin to regulate synaptic plasticity in a coordinated, cognition-promoting manner. Elevated activin levels after EE enhanced CA1 pyramidal cell excitability, facilitated synaptic transmission, and promoted long-term potentiation. These EE-induced changes were largely absent in mice expressing a dominant-negative mutant of activin receptor IB. We then interrogated the impact of activin on network oscillations and functional connectivity, using high-speed Ca (2+) imaging to study spike routing within networks formed by dissociated primary hippocampal cultures. Activin facilitated Ca2+ signaling, enhanced the network strength, and shortened the weighted characteristic path length. In the slice preparation, activin promoted theta oscillations during cholinergic stimulation. Thus, we advance activin as an activity-dependent and very early molecular effector that translates behavioral stimuli experienced during EE exposure into a set of synchronized changes in neuronal excitability, synaptic plasticity, and network activity that are all tuned to improve cognitive functions.
CRIS-Team WoS Importer:2022-03-25
Keywords: brain slice; hippocampal culture; network oscillations; neuronal connectivity; synaptic plasticity

Epigenetic control of epilepsy target genes contributes to a cellular memory of epileptogenesis in cultured rat hippocampal neurons - Kiese, Katharina; Jablonski, J.; Hackenbracht, J.; Wrosch, Jana Katharina; Groemer, Teja W.; Kornhuber, Johannes; Blümcke, Ingmar; Kobow, K. (Acta Neuropathologica Communications, 2017)
Hypersynchronous neuronal excitation manifests clinically as seizure (ictogenesis), and may recur spontaneously and repetitively after a variable latency period (epileptogenesis). Despite tremendous research efforts to describe molecular pathways and signatures of epileptogenesis, molecular pathomechanisms leading to chronic epilepsy remain to be clarified. We hypothesized that epigenetic modifications may form the basis for a cellular memory of epileptogenesis, and used a primary neuronal cell culture model of the rat hippocampus to study the translation of massive neuronal excitation into persisting changes of epigenetic signatures and pro-epileptogenic target gene expression. Increased spontaneous activation of cultured neurons was detected 3 and 7 days after stimulation with 10 ?M glutamate when compared to sham-treated time-matched controls using calcium-imaging in vitro. Chromatin-immunoprecipitation experiments revealed short-term (3 h, 7 h, and 24 h) and long-term (3 d and 2 weeks) changes in histone modifications, which were directly linked to decreased expression of two selected epilepsy target genes, e.g. excitatory glutamate receptor genes Gria2 and Grin2a. Increased promoter methylation observed 4 weeks after glutamate stimulation at respective genes suggested long-term repression of Gria2 and Grin2a genes. Inhibition of glutamatergic activation or blocking the propagation of action potentials in cultured neurons rescued altered gene expression and regulatory epigenetic modifications. Our data support the concept of a cellular memory of epileptogenesis and persisting epigenetic modifications of epilepsy target genes, which are able to turn normal into pro-epileptic neurons and circuits.
EVALuna2:7391

Feasibility and Diagnostic Accuracy of Ischemic Stroke Territory Recognition Based on Two-Dimensional Projections of Three-Dimensional Diffusion MRI Data. - Wrosch, Jana Katharina; Volbers, Bastian; Gölitz, Philipp; Gilbert, Daniel; Schwab, Stefan; Dörfler, Arnd; Kornhuber, Johannes; Groemer, Teja W. (Frontiers in Neurology, 2015)
This study was conducted to assess the feasibility and diagnostic accuracy of brain artery territory recognition based on geoprojected two-dimensional maps of diffusion MRI data in stroke patients. In this retrospective study, multiplanar diffusion MRI data of ischemic stroke patients was used to create a two-dimensional map of the entire brain. To guarantee correct representation of the stroke, a computer-aided brain artery territory diagnosis was developed and tested for its diagnostic accuracy. The test recognized the stroke-affected brain artery territory based on the position of the stroke in the map. The performance of the test was evaluated by comparing it to the reference standard of each patient’s diagnosed stroke territory on record. This study was designed and conducted according to Standards for Reporting of Diagnostic Accuracy (STARD). The statistical analysis included diagnostic accuracy parameters, cross-validation, and Youden Index optimization. After cross-validation on a cohort of 91 patients, the sensitivity of this territory diagnosis was 81% with a specificity of 87%. With this, the projection of strokes onto a two-dimensional map is accurate for representing the affected stroke territory and can be used to provide a static and printable overview of the diffusion MRI data. The projected map is compatible with other two-dimensional data such as EEG and will serve as a useful visualization tool.
Keywords: computer-aided detection and diagnosis; diffusion-weighted imaging; dimensionality reduction; magnetic resonance imaging; stroke territories; validation; visualization

Ferroptosis and PPAR-gamma in the limelight of brain tumors and edema - Yakubov, Eduard; Schmid, Sebastian; Hammer, Alexander; Chen, Daishi; Dahlmanns, Jana; Mitrovic, Ivana; Zurabashvili, Luka; Savaskan, Nicolai; Steiner, Hans Herbert; Dahlmanns, Marc (Frontiers in Oncology, 2023)
Human malignant brain tumors such as gliomas are devastating due to the induction of cerebral edema and neurodegeneration. A major contributor to glioma-induced neurodegeneration has been identified as glutamate. Glutamate promotes cell growth and proliferation in variety of tumor types. Intriguently, glutamate is also an excitatory neurotransmitter and evokes neuronal cell death at high concentrations. Even though glutamate signaling at the receptor and its downstream effectors has been extensively investigated at the molecular level, there has been little insight into how glutamate enters the tumor microenvironment and impacts on metabolic equilibration until recently. Surprisingly, the 12 transmembrane spanning tranporter xCT (SLC7A11) appeared to be a major player in this process, mediating glutamate secretion and ferroptosis. Also, PPARγ is associated with ferroptosis in neurodegeneration, thereby destroying neurons and causing brain swelling. Although these data are intriguing, tumor-associated edema has so far been quoted as of vasogenic origin. Hence, glutamate and PPARγ biology in the process of glioma-induced brain swelling is conceptually challenging. By inhibiting xCT transporter or AMPA receptors in vivo, brain swelling and peritumoral alterations can be mitigated. This review sheds light on the role of glutamate in brain tumors presenting the conceptual challenge that xCT disruption causes ferroptosis activation in malignant brain tumors. Thus, interfering with glutamate takes center stage in forming the basis of a metabolic equilibration approach.
CRIS-Team Scopus Importer:2023-08-18
Keywords: ferroptosis; glioblastoma; glutamate; peritumoral edema; SLC7A11

Functional Viability: Measurement of Synaptic Vesicle Pool Sizes - Wrosch, Jana Katharina; Groemer, Teja W. (Methods in Molecular Biology, 2017)
Neurons and their function of conveying information across a chemical synapse are highly regulated systems. Impacts on their functional viability can occur independently from changes in morphology. Here we describe a method to assess the size of synaptic vesicle pools using live cell fluorescence imaging and a genetically encoded probe (pHluorin). Assessing functional parameters such as the size of synaptic vesicle pools can be a valuable addition to common assays of neuronal cell viability as they demonstrate that key cellular functions are intact.
EVALuna2:33744

Glial Glutamate Transporter-Mediated Plasticity: System xc -/xCT/SLC7A11 and EAAT1/2 in Brain Diseases - Dahlmanns, Marc; Dahlmanns, Jana; Savaskan, Nicolai; Steiner, Hans Herbert; Yakubov, Eduard (Frontiers in Bioscience - Landmark, 2023)
Glial cells play an essential role in the complex function of the nervous system. In particular, astrocytes provide nutritive support for neuronal cells and are involved in regulating synaptic transmission. Oligodendrocytes ensheath axons and support information transfer over long distances. Microglial cells constitute part of the innate immune system in the brain. Glial cells are equipped with the glutamatecystine- exchanger xCT (SLC7A11), the catalytic subunit of system xc -, and the excitatory amino acid transporter 1 (EAAT1, GLAST) and EAAT2 (GLT-1). Thereby, glial cells maintain balanced extracellular glutamate levels that enable synaptic transmission and prevent excitotoxic states. Expression levels of these transporters, however, are not fixed. Instead, expression of glial glutamate transporters are highly regulated in reaction to the external situations. Interestingly, such regulation and homeostasis is lost in diseases such as glioma, (tumor-associated) epilepsy, Alzheimer's disease, Parkinson's disease, amyotrophic lateral sclerosis or multiple sclerosis. Upregulation of system xc - (xCT or SLC7A11) increases glutamate export from the cell, while a downregulation of EAATs decreases intracellular glutamate import. Occurring simultaneously, these reactions entail excitotoxicity and thus harm neuronal function. The release of glutamate via the antiporter system xc - is accompanied by the import of cystine-an amino acid essential in the antioxidant glutathione. This homeostasis between excitotoxicity and intracellular antioxidant response is plastic and off-balance in central nervous system (CNS) diseases. System xc - is highly expressed on glioma cells and sensitizes them to ferroptotic cell death. Hence, system xc - is a potential target for chemotherapeutic add-on therapy. Recent research reveals a pivotal role of system xc - and EAAT1/2 in tumor-associated and other types of epilepsy. Numerous studies show that in Alzheimer's disease, amyotrophic lateral sclerosis and Parkinson's disease, these glutamate transporters are dysregulated-and disease mechanisms could be interposed by targeting system xc - and EAAT1/2. Interestingly, in neuroinflammatory diseases such as multiple sclerosis, there is growing evidence for glutamate transporter involvement. Here, we propose that the current knowledge strongly suggest a benefit from rebalancing glial transporters during treatment.
CRIS-Team Scopus Importer:2023-04-14
Keywords: Alzheimer's disease; amyotrophic lateral sclerosis; GLAST; glioma; GLT-1; neuroinflammation; Parkinson's disease; SLC7A11

Presynaptic vesicular accumulation is required for antipsychotic efficacy in psychotic-like rats - Uzuneser, Taygun; Weiss, Eva Maria; Dahlmanns, Jana; Kalinichenko, Liubov; Amato, Davide; Kornhuber, Johannes; Alzheimer, Christian; Hellmann, Jan; Kaindl, Jonas; Hübner, Harald; Löber, Stefan; Gmeiner, Peter; et al. (Journal of Psychopharmacology, 2021)
Background: The therapeutic effects of antipsychotic drugs (APDs) are mainly attributed to their postsynaptic inhibitory functions on the dopamine D2 receptor, which, however, cannot explain the delayed onset of full therapeutic efficacy. It was previously shown that APDs accumulate in presynaptic vesicles during chronic treatment and are released like neurotransmitters in an activity-dependent manner triggering an auto-inhibitory feedback mechanism. Although closely mirroring therapeutic action onset, the functional consequence of the APD accumulation process remained unclear. Aims: Here we tested whether the accumulation of the APD haloperidol (HAL) is required for full therapeutic action in psychotic-like rats. Methods: We designed a HAL analog compound (HAL-F), which lacks the accumulation property of HAL, but retains its postsynaptic inhibitory action on dopamine D2 receptors. Results/outcomes: By perfusing LysoTracker fluorophore-stained cultured hippocampal neurons, we confirmed the accumulation of HAL and the non-accumulation of HAL-F. In an amphetamine hypersensitization psychosis-like model in rats, we found that subchronic intracerebroventricularly delivered HAL (0.1 mg/kg/day), but not HAL-F (0.3–1.5 mg/kg/day), attenuates psychotic-like behavior in rats. Conclusions/interpretation: These findings suggest the presynaptic accumulation of HAL may serve as an essential prerequisite for its full antipsychotic action and may explain the time course of APD action. Targeting accumulation properties of APDs may, thus, become a new strategy to improve APD action.
CRIS-Team Scopus Importer:2020-12-11
Keywords: behavior; Haloperidol; presynaptic accumulation; schizophrenia

Rewiring of neuronal networks during synaptic silencing - Wrosch, Jana Katharina; Von Einem, Vicky; Breininger, Katharina; Dahlmanns, Marc; Maier, Andreas; Kornhuber, Johannes; Groemer, Teja Wolfgang (Scientific Reports, 2017)
Analyzing the connectivity of neuronal networks, based on functional brain imaging data, has yielded new insight into brain circuitry, bringing functional and effective networks into the focus of interest for understanding complex neurological and psychiatric disorders. However, the analysis of network changes, based on the activity of individual neurons, is hindered by the lack of suitable meaningful and reproducible methodologies. Here, we used calcium imaging, statistical spike time analysis and a powerful classification model to reconstruct effective networks of primary rat hippocampal neurons in vitro. This method enables the calculation of network parameters, such as propagation probability, path length, and clustering behavior through the measurement of synaptic activity at the single-cell level, thus providing a fuller understanding of how changes at single synapses translate to an entire population of neurons. We demonstrate that our methodology can detect the known effects of drug-induced neuronal inactivity and can be used to investigate the extensive rewiring processes affecting population-wide connectivity patterns after periods of induced neuronal inactivity.
EVALuna2:33558

Synaptic Vesicle Pool Monitoring with Synapto-pHluorin - Dahlmanns, Marc; Dahlmanns, Jana (Synaptic Vesicles, 2022)
Synaptic vesicle exocytosis can be monitored with genetically encoded pH sensors in an in vitro fluorescence microscopy setup. Here, we describe a workflow starting with preparation of a primary cell culture to eventually estimate synaptic vesicle pool sizes based on electrical current-evoked vesicle release, which is reported by the synaptobrevin 2-EGFP fusion protein synapto-pHluorin (spH) that is expressed inside the synaptic vesicle membrane. The readily releasable pool and the recycling pool of synaptic vesicles are released separately in response to electrical stimulation. As vesicle reacidification is blocked in this experimental design, every released vesicle is counted only once. This spH-based approach offers different information than styryl-dye (FM dyes)-based approaches because the total synaptic pool size is measured by an alkalinization step. This provides a normalization constant for quantifying and comparing the synaptic vesicle pool sizes. In addition to investigation of basic research questions, spH-reported vesicle release is valuable to determine presynaptic effects of, e.g., pharmacological drug treatments.
CRIS-Team Scopus Importer:2022-02-11
Keywords: Live-cell fluorescence imaging; Readily releasable pool; Recycling pool; Synaptic vesicle pools; Synapto-pHluorin

Tonic activin signaling shapes cellular and synaptic properties of CA1 neurons mainly in dorsal hippocampus - Dahlmanns, Marc; Valero-Aracama, Maria Jesus; Dahlmanns, Jana; Zheng, Fang; Alzheimer, Christian (iScience, 2023)
Dorsal and ventral hippocampus serve different functions in cognition and affective behavior, but the underpinnings of this diversity at the cellular and synaptic level are not well understood. We found that the basal level of activin A, a member of the TGF-β family, which regulates hippocampal circuits in a behaviorally relevant fashion, is much higher in dorsal than in ventral hippocampus. Using transgenic mice with a forebrain-specific disruption of activin receptor signaling, we identified the pronounced dorsal-ventral gradient of activin A as a major factor determining the distinct neurophysiologic signatures of dorsal and ventral hippocampus, ranging from pyramidal cell firing, tuning of frequency-dependent synaptic facilitation, to long-term potentiation (LTP), long-term depression (LTD), and de-potentiation. Thus, the strong activin A tone in dorsal hippocampus appears crucial to establish cellular and synaptic phenotypes that are tailored specifically to the respective network operations in dorsal and ventral hippocampus.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Cellular neuroscience; Neuroscience